Finding the Sweet Spot: Wild Bees, Indigenous Peoples, and the Historic Trade in Honey and Beeswax in Northern Vietnam - Thompson, C. Michele (Asian Medicine, 2026)
When most people think of the use of animals in traditional systems of medicine, what springs to mind is one kind or another of megafauna such as rhinoceros, bears, sharks, and others. Sometimes more mundane creatures such as pangolins are included. However, invertebrates and substances produced by them have been used in Asian systems of medicine since the earliest records of materia medica from the region were created. Animals used range from shellfish and crustaceans to various insects and insect products such as cocoons, honey, and beeswax. In terms of their role in the food chain, and as pollinators, invertebrates are as crucial to the health, indeed the survival, of ecosystems in Asia and elsewhere as are megafauna. Loss and degradation of habitat is probably affecting more invertebrates than medicalization. Still, the expansion of medicalization in Asia and beyond is contributing to the danger many populations of invertebrates currently face. This article gives an overview of the place of invertebrates in Vietnamese traditional medicine and then presents a case study of two varieties of honey- and beeswax-producing bees found in northern mainland Southeast Asia and southern China: Apis dorsata F. and Apis cerana. © C. Michele Thompson, 2026. Published with license by Koninklijke Brill BV
Keywords: Arthropod; Asian traditional medicine; Creatures; Habitat; Invertebrate; Mainland; Mainland China; Southeast asia; Vietnamese; Vietnamese medicine; bees; beeswax; dept.his; ecological damage; endangered species; honey; invertebrates

Kathryn Dyt. The Nature of Kingship: The Weather-World in Nineteenth-Century Vietnam. Honolulu: University of Hawai‘i Press, 2025. - Thompson, C. Michele (Southeast Asian Studies, 2026)
Keywords: book.review; dept.his